Quizartinib Therapy for FLT3-positive Acute Myeloid Leukaemia - Mufti, Amna Faheem; Rizwan, Abdul Wahid; Azam, Adeena (Journal of the Pakistan Medical Association, 2024)
Madam, Globally, acute myeloid leukaemia (AML) is a common concern among leukaemia patients. It is the most common form of leukaemia in adults. Various genetic mutations are associated with AML. Around 30% of patients carry mutations in the FLT3 receptor, with LT3-ITD being the most common and associated with a poor prognosis1. Current treatment for this type of AML in Pakistan includes induction chemotherapy with Daunorubicin and Idarubicin, followed by allogeneic stem cell transplant or cytarabine.2 Quizartinib is a new oral agent that selectively targets the FLT3-ITD mutation and has shown promising results in a newly conducted trial, the QuANTUM-First trial. The trial shows that adding Quizartinib to standard chemotherapy with or without allogeneic stem cell transplant, followed by monotherapy with the drug for up to 3 years, resulted in improved overall survival in adults aged 18–75 years with FLT3-ITD-positive newly diagnosed AML.3 This information is crucial for physicians treating AML in Pakistan, as targeted therapeutic agents like Quizartinib must be studied and developed here. Trials should be conducted to reveal the efficacy and safety of these agents specific to the Pakistani population, as these could drastically improve the survival rate and overall prognosis of AML patients.